Designing team-based organizations new forms for knowledge work - Mohrman, Susan Albers; Cohen, Susan G.; Mohrman, Allan M. (Jossey-Bass, 1995)
Designing Team-Based Organizations breaks new ground in tackling the organizational design issues related to the implementation of teams, with a specific focus on the new designs required to support the knowledge-work components of organizations. The authors offer a field-tested design framework to help managers, consultants, human resource specialists, and students of organization design understand and develop structures and systems necessary to support the strategic deployment of teams. Drawing on over fifteen years of research and consulting with such companies as Honeywell, Hewlett Packard, Pacific Bell, General Mills, Pratt and Whitney, Pfizer, and Texas Instruments, they present a detailed, five-step design process for creating new organization designs that empower teams so that they make a real difference.
Workbook u.d.T.: Mohrman, Susan A.: Designing and leading team-based organizations
Keywords: Effectiviteit; Teamwork; Organizational effectiveness; Teams in the workplace; Teamorganisation